Potential value of rapid prostate-specific antigen decline in identifying primary resistance to abiraterone acetate and enzalutamide. (June 2014) - Caffo, Orazio; Veccia, Antonello; Maines, Francesca; Bonetta, Alberto; Spizzo, Gilbert; Galligioni, Enzo
ABSTRACT: : Aim : To identify factors predicting primary resistance to new-generation hormonal agents (NHAs), abiraterone acetate and enzalutamide in patients with castration-resistant prostate cancer (CRPC).Patients & methods : Our hospital has conducted two successive named patient NHA programs. A total of 57 patients with progressive CRPC previously treated with first-line docetaxel-based chemotherapy received standard NHA doses: abiraterone acetate 1000 mg once-daily combined with prednisone (5 mg twice daily) or enzalutamide 160 mg once-daily. Patients, who were assessed monthly to check their hematological parameters and prostate-specific antigen (PSA) levels, also underwent imaging investigations every 3–4 months. In total, 24 variables were assessed as potential predictors of primary NHA resistance.Results : Univariate analysis indicated that baseline pain and lactate dehydrogenase levels, and PSA levels after 1 month's treatment were predictive of primary NHA resistance. Only the predictive value of PSA levels after 1 month of treatment was confirmed at multivariate analysis. This factor strongly predicted progression-free and overall survival.Conclusion : Results suggest the use of a simple and rapid method of identifying patients with primary resistance to NHAs: patients not achieving a ≥50% reduction in PSA levels within the first treatment month should undergo intensive investigations to verify whether they have primary resistance to NHAs.